Organization Studies and the Legal Person - Brunsson Nils (Journal of Organizational Sociology)
The social construction of legal persons developed in the Western world about one thousand years ago has historically influenced the construction of organizations, including monasteries, guilds, cities, universities, states, associations, and businesses. Yet the notion of legal person was not present in influential, early definitions of organizations; rather organizations were understood as systems of interacting physical persons. This understanding is problematic in several respects, whereas the notion of legal person helps to explain many fundamental characteristics of organizations. Furthermore, a definition of organizations inspired by the notion of legal person makes it easier to distinguish clearly among the three phenomena that constitute the main objects of organization studies: organizations, organizing, and the organized. A clearer distinction among three concepts has the potential to revive old questions and generate new questions for organizational research.